INFLUENCE OF FEEDING CORN IMPURITIES ON RUMEN BACTERIA AND FERMENTATION CHARACTERISTICS OF SHEEP - Thaer A. M. Al-Mamouri; J. A. Tawfeeq Al-Ani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to determine the effect of replacing treated and untreated corn impurities with urea instead of wheat bran on rumen bacteria and fermentation of Awassi lambs. Five levels of treated and untreated corn impurities as 44:0%, 32:11%, 20:22%, 10:32% and 0:39% bran:impurities in a 2×5 factorial experiment/ Completely Randomized Design using forty lambs with an initial weight of 27.45 ± 2.16kg and 4-5 months old. Individual feeding was used for 70 days and rumen fluid was sampled at 0, 3, 6h after morning feeding. Results showed an increasing (p<0.05) rumen pH at zero time especially corn impurities treated with urea and increasing (p<0.05) rumen ammonia at zero time and 3h after feeding with highly significant (p<0.01) increased at 6h, and superiority increased of volatile fatty acids (VFA’s) for urea treated corn impurities (P<0.05) at zero time and after 3h of feeding, similar results for rumen bacterial count at zero time, 3h and 6h after morning feeding for two dilutions × 107 and × 109 Cfu/ml for impurities treated with urea. In conclusion, it is possible to use corn impurities instead of wheat bran, preferably treated with urea for positive increase rumen fermentation and total bacterial count in sheep.